2023
DOI: 10.3390/plants12081589
|View full text |Cite
|
Sign up to set email alerts
|

Acylphenols and Dimeric Acylphenols from the Genus Myristica: A Review of Their Phytochemistry and Pharmacology

Abstract: The genus Myristica is a medicinally important genus belonging to the Myristicaceae. Traditional medicinal systems in Asia have employed plants from the genus Myristica to treat a variety of ailments. Acylphenols and dimeric acylphenols are a rare group of secondary metabolites, which, to date, have only been identified in the Myristicaceae, in particular, in the genus Myristica. The aim of the review would be to provide scientific evidence that the medicinal properties of the genus Myristica could be attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Previous data demonstrated that, this ferocious virus is spreading and poses a great threat over four billion populations of 128 tropical and sub‐tropical countries [1] . Most importantly, approximately 390 million population infected, and among of them more than 20,000 die in a yearly basis due to dengue viral infections [2,3] . Dengue is a microorganism from Flaviviridae family, more specifically belongs to Flavivirus genus transmitted and infected the human through female Aedes mosquito bites [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data demonstrated that, this ferocious virus is spreading and poses a great threat over four billion populations of 128 tropical and sub‐tropical countries [1] . Most importantly, approximately 390 million population infected, and among of them more than 20,000 die in a yearly basis due to dengue viral infections [2,3] . Dengue is a microorganism from Flaviviridae family, more specifically belongs to Flavivirus genus transmitted and infected the human through female Aedes mosquito bites [4] .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Most importantly, approximately 390 million population infected, and among of them more than 20,000 die in a yearly basis due to dengue viral infections. [2,3] Dengue is a microorganism from Flaviviridae family, more specifically belongs to Flavivirus genus transmitted and infected the human through female Aedes mosquito bites. [4] Flavivirus genus has different four different serotypes, commonly identified as DENV-1 to DENV-4, among them DENV-1 was first detected and isolated in Japan in 1943 additionally, a new serotype DENV-5 was isolated recently in Malaysia in 2007 from the dengue the infected patient's blood (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This covers their extraction, isolation, and characterization among the respective Myristica species, discussing the structural similarities and differences within and between each group of acylphenol and dimeric acylphenol. Finally, the review also examines these compounds' in vitro pharmacological activities [10].…”
mentioning
confidence: 99%